Design, synthesis and biological evaluation of sulfur-containing 1,1-bisphosphonic acids as antiparasitic agents - Recher, Marion (2013)
As part of our efforts aimed at searching for new antiparasitic agents, 2-alkylmercaptoethyl-1,1-bisphosphonate derivatives were synthesized and evaluated against Trypanosoma cruzi, the etiologic agent of Chagas disease, and Toxoplasma gondii, the responsible agent for toxoplasmosis. Many of these sulfur-containing bisphosphonates were potent inhibitors against the intracellular form of T. cruzi, the clinically more relevant replicative form of this parasite, and tachyzoites of T. gondii targeting T. cruzi or T. gondii farnesyl diphosphate synthases (FPPSs), which constitute valid targets for the chemotherapy of these parasitic diseases. Interestingly, long chain length sulfur-containing bisphosphonates emerged as relevant antiparasitic agents. Taking compounds 37, 38, and 39 as representative members of this class of drugs, they exhibited ED50 values of 15.8 μM, 12.8 μM, and 22.4 μM, respectively, against amastigotes of T. cruzi. These cellular activities matched the inhibition of the enzymatic activity of the target enzyme (TcFPPS) having IC50 values of 6.4 μM, 1.7 μM, and 0.097 μM, respectively. In addition, these compounds were potent anti-Toxoplasma agents. They had ED50 values of 2.6 μM, 1.2 μM, and 1.8 μM, respectively, against T. gondii tachyzoites, while they exhibited a very potent inhibitory action against the target enzyme (TgFPPS) showing IC50 values of 0.024 μM, 0.025 μM, and 0.021 μM, respectively. Bisphosphonates bearing a sulfoxide unit at C-3 were also potent anti-Toxoplasma agents, particularly those bearing long aliphatic chains such as 43-45, which were also potent antiproliferative drugs against tachyzoites of T. gondii. These compounds inhibited the enzymatic activity of the target enzyme (TgFPPS) at the very low nanomolar range. These bisphosphonic acids have very good prospective not only as lead drugs but also as potential chemotherapeutic agents.